Improving Oil Palm (Elaeis guineensis Jacq) Farmer Productivity in Labusona Village, Labuhan Batu Regency - Dino Mahendra; Khairul Rizal; Yusmaidar Sepriani; Badrul Ainy Dalimunthe (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Oil palm (Elaeis guineensis Jacq.) is a plantation crop that plays a vital role in the Indonesian economy. This study aims to analyze production costs, income, and the effect of production costs on oil palm farming income in Lobusona Village, Labuhanbatu Regency. The research sample consisted of 30 farmers selected through simple random sampling. Data were analyzed using multiple linear regression. The results show that the average production cost incurred by farmers was IDR 60,600,167 per year, while the average revenue reached IDR 136,266,783 per year. This yield resulted in a net income of IDR 75,666,617 per year, or approximately IDR 24,532,139 per hectare per year. The F-test results indicate that production costs, when considered simultaneously, have a significant effect on income (Sig. 0.000 < 0.05). Meanwhile, the t-test results reveal that fertilizer costs had no significant effect, whereas pesticide and labor costs had a significant adverse effect on income. Conversely, annual production, plant age, and the price of fresh fruit bunches (FFB) had a significant positive effect. The coefficient of determination (R²) of 0.996 demonstrates that 99.6% of the variation in income is explained by the variables included in the model. These findings suggest that the efficient allocation of production costs—particularly for pesticides and labor—is crucial for improving the profitability of oil palm farming.